Services and policies of Mauban Credit and Development Cooperative - Maguyon, Richmond Ferri A. (Manila: National University, 2004)
The focus of the study is about the services and policies of Mauban Credit and Development Cooperative in Mauban, Quezon.
Title page -- Approval Sheet -- Acknowledgement -- Dedication -- Table of Contents -- List of tables -- Chapter 1. Introduction and its Background -- Chapter 2. Review of Related Literature -- Chapter 3. Research Methodology -- Chapter 4. Presentation and Analysis of data -- Chapter 5. Summary, conclusion and recommendation